Catalyst for preparing cyclohexylbenzene through alkylation of benzene and cyclohexene as well as preparation and application of catalyst
By using ultra-thin layered MWW molecular sieve supported heteropoly acid as catalyst, the problems of low selectivity and short catalyst life of benzene and cyclohexene alkylation reaction in the prior art are solved, and high selectivity and long life catalysts are achieved, reducing the generation of by-product impurities and improving the purity of cyclohexylbenzene.
Patent Information
- Application Number
- CN202311269551.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
In the prior art, the reaction of benzene with cyclohexylbenzene to alkylation of cyclohexylbenzene has problems such as low product selectivity, high methylcyclopentylbenzene content and short catalyst life.
The ultra-thin layered MWW molecular sieve supported heteropoly acids are used as catalysts to synthesize ultra-thin layered MWW molecular sieve by the dual-template method. Using its excellent diffusion properties and high acid amount, the selectivity and service life of the catalyst are improved, so that the reaction is carried out at a lower temperature and the generation of by-product impurities is reduced.
The selectivity of the alkylation reaction between benzene and cyclohexene and the service life of the catalyst are improved, the generation of the by-product impurity methylcyclopentylbenzene is reduced, the separation energy consumption is reduced, and the purity of cyclohexylbenzene is improved.
Smart Images

Figure CN119702078A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fine chemical production, and in particular to a catalyst for preparing cyclohexylbenzene by alkylation of benzene and cyclohexene, and the preparation and application of the catalyst. Background Art
[0002] Cyclohexylbenzene (CHB) can be used as an electrolyte additive for lithium-ion secondary batteries, which can improve the battery's anti-overcharge performance, reduce the electrolyte conductivity, make the battery safer to use, and has high value. CHN is also one of the raw materials for synthesizing liquid crystal material thin film transistors (TFTs), which can improve its photochemical stability and reduce viscosity; cyclohexylbenzene also has a high cetane number and can be used as a diesel cetane number blending component.
[0003] In the field of phenol-ketone manufacturing industry, cyclohexylbenzene can be used to produce phenol and cyclohexanone through oxidation and acid decomposition reaction, replacing the process of preparing phenol by isopropylbenzene method and solving the problem of acetone overcapacity. The downstream product of the co-product cyclohexanone is caprolactam, which is an important raw material for manufacturing synthetic fibers and has high application value.
[0004] Cyclohexylbenzene can be prepared by Friedel-Crafts alkylation of benzene, biphenyl hydrogenation or benzene hydroalkylation. The latter two methods have problems such as low yield of target product, difficulty in catalyst preparation and high cost, which need to be improved. Therefore, Friedel-Crafts alkylation of benzene is currently the most economical preparation method.
[0005] CN1982263A discloses a method for preparing cyclohexylbenzene from benzene and cyclohexanol under the catalysis of liquid acid such as sulfuric acid and AlCl3. The yield of cyclohexylbenzene reaches 90%. However, due to the use of inorganic liquid acid, there are prominent problems such as high energy consumption for product separation, large waste production, equipment corrosion, and intermittent reaction. Therefore, it is only suitable for small-batch production.
[0006] CN101219922A, CN101811924A, CN109369322A, CN110606796A, etc. disclose a series of methods for preparing cyclohexylbenzene using acidic ionic liquids as catalysts, which can achieve the effect of inorganic liquid acid catalysis and have the advantage that the catalyst can be recycled multiple times. However, the preparation of ionic liquids requires anhydrous and oxygen-free conditions, and the preparation cost is high. Currently, the methods are still in the laboratory research and development stage.
[0007] The process of preparing cyclohexylbenzene by catalyzing the alkylation of benzene and cyclohexene under liquid-solid phase conditions using molecular sieve solid acid as a catalyst has the advantages of low product separation difficulty and continuous production, and has always been regarded as a potential alternative process for liquid acid catalysis. CN108435234A discloses a method for applying a molecular sieve-supported heteropoly acid catalyst in the synthesis of cyclohexylbenzene, using an ultra-stabilized USY molecular sieve as a carrier, loading heteropoly acids such as phosphotungstic acid, and preparing a catalyst to catalyze the alkylation of benzene and cyclohexene in an intermittent high-pressure reactor, the reaction temperature is 100-200°C, the conversion rate can reach 99%, and the cyclohexylbenzene selectivity is 94%; however, the reaction time requires 2-8h, and it is an intermittent reaction, the efficiency is low, and it is not suitable for large-scale continuous production, which reflects the low catalytic efficiency of the catalyst.
[0008] Since the molecular size of the alkylation product of benzene and cyclohexene is relatively large, it is very easy to cause clogging of the pores when using molecular sieves as catalysts, thereby deactivating them. Although increasing the reaction temperature can promote the diffusion of these molecules, it will also cause an increase in side reactions and improve the selectivity of key impurities such as methylcyclopentylbenzene. Among them, the boiling point of methylcyclopentylbenzene is close to that of cyclohexylbenzene, which makes it difficult to separate by distillation. Therefore, it is difficult to develop a catalytic reaction system that has both high selectivity and long catalyst life. Summary of the invention
[0009] In view of the outstanding problems in the prior art of the alkylation reaction of benzene with cyclohexene to produce cyclohexylbenzene, such as low product selectivity, high content of by-product methylcyclopentylhexylbenzene, and short catalyst life, the present invention provides a catalyst for the alkylation of benzene with cyclohexene to produce cyclohexylbenzene, and its preparation and application. The use of the catalyst of the present invention can improve its selectivity and service life, so that the alkylation reaction of benzene with cyclohexene can be carried out at a lower reaction temperature, thereby reducing the selectivity of the key by-product impurity methylcyclopentylbenzene.
[0010] The first aspect of the present invention provides a catalyst for the alkylation of benzene with cyclohexene to produce cyclohexylbenzene, the catalyst comprising an ultra-thin layered MWW molecular sieve and a heteropoly acid, the layer thickness of the ultra-thin layered MWW molecular sieve being 5 to 10 nm; the heteropoly acid being one or more of phosphotungstic acid (HPW), silicotungstic acid (HSiW), and phosphomolybdic acid (HPMo), preferably phosphotungstic acid.
[0011] Furthermore, the SiO2 / Al2O3 molar ratio of the ultra-thin layered MWW molecular sieve is 10-100, preferably 20-40.
[0012] Furthermore, in the catalyst, based on the total weight of the MWW molecular sieve and the binder in terms of oxide, the heteropoly acid content is 10 wt% to 100 wt%, preferably 40 wt% to 80 wt%, calculated as heteropoly acid molecules excluding water.
[0013] Furthermore, the catalyst also includes a binder, and the binder is one or more of aluminum oxide or silicon oxide.
[0014] Furthermore, in the catalyst, the content of the binder in terms of oxide is 3% to 15%, preferably 5% to 10%, based on the weight of the catalyst.
[0015] The second aspect of the present invention provides a method for preparing the above catalyst, comprising the following steps:
[0016] (1) mixing a silicon source, an aluminum source, an alkali source, water, a first template (T1) and a second template (T2), and crystallizing them to obtain an ultra-thin layered MWW molecular sieve;
[0017] (2) acid-exchanging, shaping, and calcining the ultra-thin layered MWW molecular sieve obtained in step (1) to obtain the catalyst intermediate;
[0018] (3) The catalyst intermediate obtained in step (2) is impregnated with a heteropolyacid aqueous solution in the presence of a surfactant, and then calcined to obtain the catalyst.
[0019] Furthermore, in step (1), the alkali source, water, the first template (T1) and the second template (T2) are first mixed, then the silicon source is added and stirred, and finally the aluminum source is added, and then aged at 0-40° C. for 1-12 hours and then crystallized.
[0020] Furthermore, in step (1), the silicon source is selected from at least one of silicon dioxide, silica sol, white carbon, water glass, sodium silicate or tetraethyl silicate, preferably silicon dioxide.
[0021] Furthermore, in step (1), the aluminum source is selected from at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, aluminum isopropoxide, aluminum sol or aluminum hydroxide, and is preferably aluminum nitrate.
[0022] Furthermore, in step (1), the alkali source is selected from at least one of sodium hydroxide or potassium hydroxide, preferably sodium hydroxide.
[0023] Furthermore, in step (1), the first template (T1) is selected from at least one of hexamethyleneimine (HMI), tetrahydropyrrole, hexahydropyridine (PI), 2-methylhexahydropyridine or heptamethyleneimine, preferably at least one of hexamethyleneimine (HMI) and hexahydropyridine (PI).
[0024] Furthermore, in step (1), the second template (T2) is selected from at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, didecyldimethylammonium chloride, tetradecyldimethylbenzylammonium chloride or octadecyltrimethylammonium bromide, preferably at least one of hexadecyltrimethylammonium bromide (CTAB) and dodecyltrimethylammonium chloride (DTAC).
[0025] Furthermore, in step (1), the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the alkali is calculated as OH - The molar ratio of the feed is: SiO2 / Al2O3 is 10-100, preferably 20-40; OH - / SiO2 is 0-0.40, preferably 0.05-0.15; H2O / SiO2 is 10-50, preferably 20-30; T1 / SiO2 is 0.05-1.0, preferably 0.1-0.5; T2 / SiO2 is 0.001-0.1, preferably 0.01-0.04.
[0026] Furthermore, in step (1), the crystallization adopts dynamic crystallization, the stirring rate is 10-200 rpm, preferably 20-100 rpm; the crystallization temperature is 100-200° C., preferably 150-180° C.; the crystallization time is 24-144 h, preferably 48-96 h.
[0027] Furthermore, in step (1), after the crystallization is completed, the product is washed and dried for later use, wherein the washing and drying are conventional operations in the art.
[0028] Furthermore, in step (1), the SiO2 / Al2O3 molar ratio of the ultra-thin layered MWW molecular sieve is 10 to 100, preferably 20 to 40.
[0029] Furthermore, in step (2), the acid exchange conditions include: temperature of 20-100°C, preferably 65-95°C; time of 0.5-24h / time, preferably 3-8h / time; acid concentration of 0.001-2mol / L, preferably 0.01-0.5mol / L; acid exchange times of 1-6 times, preferably 2-4 times. The mass ratio of acid solution to molecular sieve is 2-20, preferably 5-10.
[0030] Furthermore, in step (2), the acid is an organic acid and / or an inorganic acid; preferably, the acid is at least one of oxalic acid, citric acid, formic acid, acetic acid, propionic acid, sulfuric acid, nitric acid and hydrochloric acid.
[0031] Furthermore, in step (2), after the acid exchange is completed, the product is washed and dried for later use, wherein washing and drying are conventional operations in the art.
[0032] Furthermore, in step (2), the binder used in the molding process is at least one of pseudo-boehmite, silica sol, γ-alumina, aluminum hydroxide or white carbon black, preferably pseudo-boehmite or silica sol. The weight content of the binder in the catalyst is 3% to 15%, preferably 5% to 10%, calculated as oxide.
[0033] Furthermore, in step (2), the calcination temperature is 350-650° C., preferably 500-600° C., and the calcination time is 1-10 h, preferably 2-8 h.
[0034] Furthermore, in step (3), the catalyst intermediate, i.e. the ultra-thin MWW molecular sieve after forming, is immersed in a heteropolyacid aqueous solution in the presence of a surfactant, and the catalyst is obtained after draining, drying and calcining. The immersion is an equal volume immersion. The calcination conditions are a temperature of 350 to 550° C., preferably 400 to 500° C., and a time of 1 to 12 hours, preferably 3 to 6 hours.
[0035] Furthermore, in step (3), the surfactant is at least one of a nonionic surfactant or an anionic surfactant. The nonionic surfactant is poly-[ethylene glycol x -Propylene glycol y -Ethylene glycol z ] The triblock oligomer has a molecular weight range of 1100 to 14600, preferably 4400 to 8000. The anionic surfactant is one or more of n-hexadecylbenzenesulfonic acid, hexadecyltrimethyltoluenesulfonic acid, and dodecylbenzenesulfonic acid. The mass ratio of the surfactant to the MWW molecular sieve is 0.001 to 0.10, preferably 0.01 to 0.05.
[0036] Furthermore, in step (3), the heteropoly acid is one or more of phosphotungstic acid (HPW), silicotungstic acid (HSiW), phosphomolybdic acid (HPMo), preferably phosphotungstic acid. The mass concentration of the heteropoly acid aqueous solution is 8.3% to 83.3%, preferably 33.3% to 66.7%. In the catalyst preparation process, the amount of the heteropoly acid is such that the loading amount of the heteropoly acid in the final catalyst is 10 to 100 wt%, preferably 40 to 80 wt%, based on the total weight of the MWW molecular sieve and the binder in terms of oxide.
[0037] The third aspect of the present invention provides a method for preparing cyclohexylbenzene by alkylation of benzene and cyclohexene, comprising an alkylation reaction of benzene and cyclohexene on the above catalyst.
[0038] Furthermore, the method adopts a fixed bed reactor.
[0039] Furthermore, in the method for alkylating benzene with cyclohexene to prepare cyclohexylbenzene, the molar ratio of raw benzene to cyclohexene is 3 to 30, preferably 5 to 15; the water content in the raw material is <100 mg / kg, preferably <50 mg / kg; the total nitrogen content is <0.1 mg / kg, preferably <0.05 mg / kg; and the total sulfur content is <0.1 mg / kg, preferably <0.05 mg / kg.
[0040] Furthermore, in the method for preparing cyclohexylbenzene by alkylation of benzene and cyclohexene, the raw materials benzene and cyclohexene can be selectively pretreated by dehydration and de-alkalization according to the impurity content. The pretreatment can be carried out by adsorption, for example, using 13X molecular sieve as an adsorbent.
[0041] Furthermore, in the method for preparing cyclohexylbenzene by alkylation of benzene and cyclohexene, the total mass space velocity of the raw materials benzene and cyclohexene is 0.1 to 6.0 h -1 , preferably 1.0~4.0h -1 .
[0042] Furthermore, the pressure of the alkylation reaction is 1.0 to 4.0 MPa, preferably 1.5 to 2.5 MPa.
[0043] Furthermore, the temperature of the alkylation reaction is 80 to 200°C, preferably 110 to 150°C.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) The present invention uses a heteropolyacid supported on an ultra-thin layered MWW molecular sieve as a catalyst, wherein the ultra-thin layered MWW molecular sieve is synthesized by a dual template method, and its excellent diffusion performance and high acid content are utilized to improve its selectivity and service life, so that the alkylation reaction of benzene and cyclohexene is carried out at a lower reaction temperature, thereby reducing the selectivity of the key by-product impurity methylcyclopentylbenzene.
[0046] (2) The ultra-thin layered MWW molecular sieve supported heteropolyacid catalyst provided by the present invention has better alkylation activity and selectivity. Benzene and cyclohexene can be reacted at a lower reaction temperature (preferably 110-150°C). Cyclohexene does not need to be fed in stages to achieve good selectivity. The selectivity of the key by-product methylcyclopentylbenzene is greatly reduced to below 1.5%, which can greatly reduce separation energy consumption and improve the purity of the product cyclohexylbenzene.
[0047] (3) Under the reaction process conditions used in the present invention, the catalyst has a long service life, and the one-way life can reach more than 1500 hours, which can meet the requirements of industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1XRD pattern of the catalyst M1 synthesized in Example 1;
[0049] Figure 2 SEM photograph of catalyst M1 synthesized in Example 1. DETAILED DESCRIPTION
[0050] The present invention will be further described below by way of examples.
[0051] In the present invention, the loading amount of the heteropoly acid in the catalyst active component is set by X-ray fluorescence spectroscopy (XRF).
[0052] In the present invention, the XRD spectrum of the catalyst is characterized by a Bruker D8 Advanced X-ray diffractometer for phase analysis of the catalyst sample, with a scanning range of 3 to 50°, a step length of 0.05°, and a scanning speed of 4° / min.
[0053] In the present invention, the SEM photograph of the catalyst is observed using a FEI Nova NanoSEM 450 electron microscope.
[0054] In the present invention, the product after the alkylation reaction of benzene and cyclohexene is analyzed by gas chromatography (GC-FID), and key indicators such as cyclohexene conversion rate, cyclohexylbenzene selectivity, cyclohexylation selectivity, and methylcyclopentylhexylbenzene selectivity are calculated according to the following formulas:
[0055] Cyclohexene conversion rate = (cyclohexene mass percentage before reaction - cyclohexene mass percentage after reaction) / (cyclohexene mass percentage before reaction) × 100%;
[0056] Cyclohexylbenzene selectivity = (cyclohexylbenzene mass percentage) / (total mass percentage of all products and by-products) × 100%;
[0057] Cyclohexylation selectivity = (mass percentage of cyclohexylbenzene + dicyclohexylbenzene) / (total mass percentage of all products and by-products) × 100%;
[0058] Methylcyclopentylbenzene selectivity=(mass percentage of methylcyclopentylbenzene) / (total mass percentage of all products and by-products)×100%.
[0059] [Example 1]
[0060] (1) Add 3.6g NaOH, 11.88g hexamethyleneimine (HMI), and 1.64g hexadecyltrimethylammonium bromide (CTAB) to 139.1g water, and after fully dissolving and mixing, add 18.00g silica powder, stir vigorously, and then add 7.50g aluminum nitrate nonahydrate. Age at room temperature (25°C) for 6h, and transfer to a high-pressure bomb equipped with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 165°C, the crystallization time is 96h, and the rotation speed is 40rpm. After the crystallization is completed, wash with pure water, dry, and set aside. The synthesis ratio of the above molecular sieve is: 1SiO2:1 / 30Al2O3:0.10OH - :25H2O:0.40HMI:0.015CTAB.
[0061] (2) The above molecular sieve intermediate product (SiO2 / Al2O3 molar ratio of 29.5, thickness of 5.0-7.5 nm) was exchanged in 0.1 mol / L hydrochloric acid solution at 80°C for 5 h / time for 4 times. After washing and drying, pseudo-boehmite and dilute nitric acid were added to form a catalyst cylindrical strip of Φ1.5 mm and 3-10 mm in length. The amount of pseudo-boehmite added was calculated on a dry basis and accounted for 10% of the total weight of the catalyst. The catalyst was calcined in air at 525°C for 5 h.
[0062] (3) The ultra-thin MWW molecular sieve formed above was immersed in a 50.0% phosphotungstic acid (HPW) aqueous solution, and a surfactant poly-[ethylene glycol] x -Propylene glycol y -Ethylene glycol z ] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.04. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M1 is prepared, wherein the phosphotungstic acid loading is 61.2wt%.
[0063] [Example 2]
[0064] Compared with Example 1, the only difference is that in step (3), the ultra-thin MWW molecular sieve after molding is immersed in a 66.7% phosphotungstic acid (HPW) aqueous solution, and then drained, dried, and calcined at 475°C for 4 hours to prepare an alkylation catalyst M2, in which the HPW loading is 79.6%.
[0065] [Example 3]
[0066] Compared with Example 1, the only difference is that in step (3), the ultra-thin MWW molecular sieve after molding is immersed in a 33.3% phosphotungstic acid (HPW) aqueous solution, and then drained, dried, and calcined at 475°C for 4 hours to prepare an alkylation catalyst M3, in which the HPW loading is 41.0%.
[0067] [Example 4]
[0068] (1) Add 4.1g NaOH, 11.9g hexamethyleneimine (HMI), and 1.6g hexadecyltrimethylammonium bromide (CTAB) to 139.8g water, fully dissolve and mix, then add 18.0g silica powder, stir vigorously, add 9.0g aluminum nitrate nonahydrate, age at room temperature for 6h, and transfer to a high-pressure bomb equipped with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 155°C, the crystallization time is 84h, and the rotation speed is 40rpm. After the crystallization is completed, wash with pure water, dry, and set aside. The synthesis ratio of the above molecular sieve is: 1SiO2:1 / 25Al2O3:0.10OH - :25H2O:0.40HMI:0.015CTAB.
[0069] (2) The intermediate product obtained above (SiO2 / Al2O3 molar ratio was measured to be 24.3, thickness was 5.0-7.5 nm) was exchanged in 0.1 mol / L hydrochloric acid solution, the exchange temperature was 80°C, the time was 5 h / time, and the exchange was repeated 4 times. After washing and drying, pseudo-boehmite and dilute nitric acid were added to form a catalyst cylindrical strip with a diameter of 1.5 mm and a length of 3-10 mm. The amount of pseudo-boehmite added was calculated on a dry basis and accounted for 10% of the total weight of the catalyst. The catalyst was calcined in air at 525°C for 5 h.
[0070] (3) The ultra-thin MWW molecular sieve formed above was immersed in a 50.0% phosphotungstic acid (HPW) aqueous solution, and a surfactant poly-[ethylene glycol] x -Propylene glycol y -Ethylene glycol z ] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.04. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M4 is prepared, in which the phosphotungstic acid loading is 60.8wt%.
[0071] [Example 5]
[0072] (1) Add 2.5g NaOH, 13.4g hexamethyleneimine (HMI), and 2.18g hexadecyltrimethylammonium bromide (CTAB) to 121.8g water, fully dissolve and mix, then add 18.0g silica powder, stir vigorously, add 5.6g aluminum nitrate nonahydrate, age at room temperature for 6h, and transfer to a high-pressure bomb equipped with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 165°C, the crystallization time is 96h, and the rotation speed is 40rpm. After the crystallization is completed, wash with pure water, dry, and set aside. The synthesis ratio of the above molecular sieve is: 1SiO2:1 / 40Al2O3:0.06OH- :22H2O:0.45HMI:0.020CTAB.
[0073] (2) The intermediate product obtained above (SiO2 / Al2O3 molar ratio was measured to be 38.9, thickness was 5.0-7.5 nm) was exchanged in 0.1 mol / L hydrochloric acid solution, the exchange temperature was 80°C, the time was 5 h / time, and the exchange was repeated 4 times. After washing and drying, pseudo-boehmite and dilute nitric acid were added to form a catalyst cylindrical strip with a diameter of 1.5 mm and a length of 3-10 mm. The amount of pseudo-boehmite added was calculated on a dry basis and accounted for 10% of the total weight of the catalyst. The catalyst was calcined in air at 525°C for 5 h.
[0074] (3) The ultra-thin MWW molecular sieve formed above was immersed in a 50.0% phosphotungstic acid (HPW) aqueous solution, and a surfactant poly-[ethylene glycol] x -Propylene glycol y -Ethylene glycol z ] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.04. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M5 is prepared, in which the phosphotungstic acid loading is 61.0wt%.
[0075] [Example 6]
[0076] (1) Add 3.6g NaOH, 11.88g hexamethyleneimine (HMI), and 2.73g hexadecyltrimethylammonium bromide (CTAB) to 139.1g water, and after fully dissolving and mixing, add 18.00g silica powder, stir vigorously, and then add 7.50g aluminum nitrate nonahydrate. Age at room temperature for 6h, and transfer to a high-pressure bomb equipped with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 165°C, the crystallization time is 144h, and the rotation speed is 40rpm. After the crystallization is completed, wash with pure water, dry, and set aside. The synthesis ratio of the above molecular sieve is: 1SiO2:1 / 30Al2O3:0.10OH - :25H2O:0.40HMI:0.030CTAB.
[0077] (2) The molecular sieve intermediate product (SiO2 / Al2O3 molar ratio of 29.3, thickness of 5.0-7.5 nm) was exchanged in 0.1 mol / L hydrochloric acid solution at 80°C for 5 h / time for 4 times. After washing and drying, pseudo-boehmite and dilute nitric acid were added to form a catalyst cylindrical strip of Φ1.5 mm and 3-10 mm in length. The amount of pseudo-boehmite added was calculated on a dry basis and accounted for 10% of the total weight of the catalyst. The catalyst was calcined in air at 525°C for 5 h.
[0078] (3) The ultra-thin MWW molecular sieve formed above was immersed in a 50.0% phosphotungstic acid (HPW) aqueous solution, and a surfactant poly-[ethylene glycol] x -Propylene glycol y -Ethylene glycol z ] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.04. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M6 is prepared, in which the phosphotungstic acid loading is 61.4wt%.
[0079] [Example 7]
[0080] (1) Add 3.6g NaOH, 10.20g hexahydropyridine (PI), and 1.64g hexadecyltrimethylammonium bromide (CTAB) to 139.1g water, and after fully dissolving and mixing, add 18.00g silica powder, stir vigorously, and then add 7.50g aluminum nitrate nonahydrate. Age at room temperature for 6h, and transfer to a high-pressure bomb equipped with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 165°C, the crystallization time is 96h, and the rotation speed is 40rpm. After the crystallization is completed, wash with pure water, dry, and set aside. The synthesis ratio of the above molecular sieve is: 1SiO2:1 / 30Al2O3:0.10OH - :25H2O:0.4PI:0.015CTAB.
[0081] (2) The molecular sieve intermediate product (SiO2 / Al2O3 molar ratio of 29.7, thickness of 5.0-7.5 nm) was exchanged in 0.1 mol / L hydrochloric acid solution at 80°C for 5 h / time for 4 times. After washing and drying, pseudo-boehmite and dilute nitric acid were added to form a catalyst cylindrical strip of Φ1.5 mm and 3-10 mm in length. The amount of pseudo-boehmite added was calculated on a dry basis and accounted for 10% of the total weight of the catalyst. The catalyst was calcined in air at 525°C for 5 h.
[0082] (3) The ultra-thin MWW molecular sieve formed above was immersed in a 50.0% phosphotungstic acid (HPW) aqueous solution, and a surfactant poly-[ethylene glycol] x -Propylene glycol y -Ethylene glycol z ] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.04. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M7 is prepared, in which the phosphotungstic acid loading is 60.7wt%.
[0083] [Example 8]
[0084] (1) Add 3.6g NaOH, 11.88g hexamethyleneimine (HMI), and 1.19g dodecyltrimethylammonium chloride (DTAC) to 139.1g water, fully dissolve and mix, then add 18.00g silica powder, stir vigorously, add 7.50g aluminum nitrate nonahydrate, age at room temperature for 6h, and transfer to a high-pressure bomb equipped with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 165°C, the crystallization time is 96h, and the rotation speed is 40rpm. After the crystallization is completed, wash with pure water, dry, and set aside. The synthesis ratio of the above molecular sieve is: 1SiO2:1 / 30Al2O3:0.10OH - :25H2O:0.40HMI:0.015DTAC.
[0085] (2) The above molecular sieve intermediate product (SiO2 / Al2O3 molar ratio of 28.9, thickness of 5.0-7.5 nm) was exchanged in 0.1 mol / L hydrochloric acid solution at 80°C for 5 h / time for 4 times. After washing and drying, pseudo-boehmite and dilute nitric acid were added to form a catalyst cylindrical strip of Φ1.5 mm and 3-10 mm in length. The amount of pseudo-boehmite added was calculated on a dry basis and accounted for 10% of the total weight of the catalyst. The catalyst was calcined in air at 525°C for 5 h.
[0086] (3) The ultra-thin MWW molecular sieve formed above was immersed in a 50.0% phosphotungstic acid (HPW) aqueous solution, and a surfactant poly-[ethylene glycol] x -Propylene glycol y -Ethylene glycol z ] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.04. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M8 is prepared, wherein the phosphotungstic acid loading is 61.0wt%.
[0087] [Example 9]
[0088] Compared with Example 1, the only difference is that 0.2 mol / L citric acid is used instead of 0.1 mol / L hydrochloric acid. Alkylation catalyst M9 is prepared, wherein the phosphotungstic acid loading is 60.8 wt%.
[0089] [Example 10]
[0090] The ultra-thin MWW molecular sieve prepared in step (2) of Example 1 was immersed in a 50.0% phosphotungstic acid (HPW) aqueous solution, and a surfactant, poly-[ethylene glycol] x -Propylene glycol y -Ethylene glycol z] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.02. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M10 is prepared, in which the phosphotungstic acid loading is 61.3wt%.
[0091] [Example 11]
[0092] Changing the type of surfactant used for impregnation
[0093] The ultra-thin MWW molecular sieve prepared in step (2) of Example 1 was immersed in a 50.0% phosphotungstic acid (HPW) aqueous solution, and a surfactant n-hexadecylbenzenesulfonic acid was added to the aqueous solution, and the mass ratio of the added surfactant to the MWW molecular sieve was 0.04. After draining, drying, and calcining at 475°C for 4h, an alkylation catalyst M11 was prepared, in which the phosphotungstic acid loading was 61.4wt%.
[0094] [Example 12]
[0095] Compared with Example 1, the only difference is that the ultra-thin MWW molecular sieve prepared in step (2) of Example 1 is immersed in a 50.0% silicotungstic acid (HSiW) aqueous solution, and a surfactant poly-[ethylene glycol] is added to the aqueous solution. x -Propylene glycol y -Ethylene glycol z ] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.04. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M12 is prepared, in which the silicotungstic acid loading is 60.5wt%.
[0096] [Example 13]
[0097] Compared with Example 1, the only difference is that the ultra-thin MWW molecular sieve prepared in step (2) of Example 1 is immersed in a 50.0% phosphomolybdic acid (HPMo) aqueous solution, and a surfactant poly-[ethylene glycol] is added to the aqueous solution. x -Propylene glycol y -Ethylene glycol z ] triblock oligomer, molecular weight of 5800, the mass ratio of surfactant added to MWW molecular sieve is 0.04. After draining, drying, and calcining at 475°C for 4h, alkylation catalyst M13 is prepared, in which the phosphomolybdic acid loading is 59.8wt%.
[0098] [Comparative Example 1]
[0099] Add 3.6g NaOH, 11.88g hexamethyleneimine (HMI), 1.64g hexadecyltrimethylammonium bromide (CTAB) to 139.1g water, fully dissolve and mix, then add 18.00g silica powder, stir vigorously, add 7.50g aluminum nitrate nonahydrate, age at room temperature for 6h, and transfer to a high-pressure bomb equipped with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 165°C, the crystallization time is 96h, and the rotation speed is 40rpm. After the crystallization is completed, wash with pure water, dry, and set aside. The synthesis ratio of the above molecular sieve is: 1SiO2:1 / 30Al2O3:0.10OH - :25H2O:0.40HMI:0.015CTAB.
[0100] The molecular sieve intermediate product (SiO2 / Al2O3 molar ratio of 29.5, thickness of 5.0-7.5nm) was exchanged in 0.1mol / L hydrochloric acid solution at 80°C for 5h / time for 4 times. After washing and drying, pseudo-boehmite and dilute nitric acid were added to form a catalyst cylindrical strip of Φ1.5mm and 3-10mm in length. The amount of pseudo-boehmite added was calculated on a dry basis and accounted for 10% of the total weight of the catalyst. The catalyst was calcined in air at 525°C for 5h to prepare the alkylation catalyst C1.
[0101] [Comparative Example 2]
[0102] Compared with Example 1, the only difference is that in step (1) during the preparation of the molecular sieve, no CTAB is added.
[0103] Add 3.6g NaOH and 11.88g hexamethyleneimine (HMI) to 139.1g water, fully dissolve and mix, then add 18.00g silica powder, stir vigorously, add 7.50g aluminum nitrate nonahydrate, age at room temperature for 6h, and transfer to a high-pressure bomb equipped with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 165°C, the crystallization time is 96h, and the rotation speed is 40rpm. After the crystallization is completed, wash with pure water, dry, and set aside. The synthesis ratio of the above molecular sieve is: 1SiO2:1 / 30Al2O3:0.10OH - :25H2O:0.40HMI:0CTAB.
[0104] The prepared alkylation catalyst is recorded as C2, in which the loading amount of phosphotungstic acid is 61.1 wt %.
[0105] [Comparative Example 3]
[0106] Compared with Example 1, the difference is:
[0107] Commercially available USY molecular sieve (SiO2 / Al2O3=6.1), pseudo-boehmite and dilute nitric acid were mixed and molded into catalyst cylindrical bars of Φ1.5mm and 3-10mm in length. The amount of pseudo-boehmite added was 10% of the total weight of the catalyst on a dry basis. The catalyst was calcined in air at 525°C for 5h, then immersed in a 60.0% phosphotungstic acid (HPW) aqueous solution, drained, dried, and calcined at 475°C for 4h to prepare an alkylation catalyst C3, in which the phosphotungstic acid loading was 61.2wt%.
[0108] [Comparative Example 4]
[0109] Compared with Example 1, the only difference is that an equal mole of dipentyldimethylammonium iodide (DPenDMAI) is used to replace hexadecyltrimethylammonium bromide (CTAB).
[0110] Comparative Example 4 prepared an alkylation catalyst C4, in which the phosphotungstic acid loading was 60.2 wt %.
[0111]
Application Example 1
[0112] Cyclohexylbenzene is prepared by alkylation reaction of benzene and cyclohexene under the catalysis of the above-prepared catalyst. The raw materials benzene and cyclohexene are dehydrated with 13X molecular sieve and pretreated with de-alkalization, and then fully mixed. The molar ratio of benzene to cyclohexene is 10; the water content in the raw material is 15 mg / kg, the total nitrogen content is 0.03 mg / kg, and the total sulfur content is 0.05 mg / kg. The catalysts prepared in Examples 1 to 13 and Comparative Examples 1 to 4 are respectively loaded in a fixed bed reactor, with a loading amount of 3.0 g. Under the conditions of a reaction temperature of 130°C and a pressure of 2.0 MPa, the raw materials configured and pretreated are introduced at a flow rate of 6.0 g / h, that is, the raw material space velocity is 2.0 h -1 The reaction products were analyzed and calculated by gas chromatography, and the results are shown in Table 1.
[0113] Table 1
[0114]
[0115] * Data with a response time of 72 hours,
[0116] **Reaction time for cyclohexene conversion > 99.8%.
[0117]
Application Example 2
[0118] Cyclohexylbenzene is prepared by alkylation reaction of benzene and cyclohexene under the catalysis of the above-prepared catalyst. The raw materials benzene and cyclohexene are dehydrated with 13X molecular sieve and pretreated with de-alkalization, and then fully mixed. The molar ratio of benzene to cyclohexene is 12.5; the water content in the raw material is 56 mg / kg, the total nitrogen content is 0.05 mg / kg, and the total sulfur content is 0.07 mg / kg. The catalysts prepared in Example 1 and Comparative Example 1 are respectively loaded in a fixed bed reactor with a loading amount of 3.0 g. Under the conditions of reaction temperature of 145°C and pressure of 2.5 MPa, the raw material configured and pretreated as above is introduced at a flow rate of 12.0 g / h, that is, the raw material space velocity is 4.0 h -1 The reaction products were analyzed and calculated by gas chromatography, and the results are shown in 2.
[0119] Table 2
[0120]
[0121] * Data with a response time of 72 hours,
[0122] **Reaction time for cyclohexene conversion > 99.8%.
[0123]
Application Example 3
[0124] Cyclohexylbenzene is prepared by alkylation reaction of benzene and cyclohexene under the catalysis of the above-prepared catalyst. The raw materials benzene and cyclohexene are dehydrated with 13X molecular sieve and pretreated with de-alkalizing substances, and then fully mixed. The molar ratio of benzene to cyclohexene is 10; the water content in the raw materials is 15 mg / kg, the total nitrogen content is 0.03 mg / kg, and the total sulfur content is 0.05 mg / kg. The catalyst prepared in Example 1 and Comparative Example 1 is loaded in a fixed bed reactor with a loading amount of 3.0 g. Under the conditions of reaction temperature of 170°C and pressure of 2.0 MPa, the raw materials configured and pretreated as above are introduced at a flow rate of 6.0 g / h, that is, the raw material space velocity is 2.0 h -1 The reaction products were analyzed and calculated by gas chromatography, and the results are shown in Table 3.
[0125] Table 3
[0126]
[0127] * Data with a response time of 72 hours,
[0128] **Reaction time for cyclohexene conversion > 99.8%.
[0129] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for the alkylation of benzene with cyclohexene to produce cyclohexylbenzene, the catalyst comprising an ultra-thin layered MWW molecular sieve and a heteropoly acid, wherein the layer thickness of the ultra-thin layered MWW molecular sieve is 5 to 10 nm; the heteropoly acid is one or more of phosphotungstic acid, silicotungstic acid, and phosphomolybdic acid, preferably phosphotungstic acid.
2. The catalyst according to claim 1, characterized in that: The SiO2 / Al2O3 molar ratio of the ultra-thin layered MWW molecular sieve is 10-100, preferably 20-40.
3. The catalyst according to claim 1, characterized in that: The catalyst includes a binder, and the binder is one or more of aluminum oxide or silicon oxide; Preferably, in the catalyst, the content of the binder in terms of oxide is 3% to 15%, preferably 5% to 10%, based on the weight of the catalyst.
4. The catalyst according to claim 1, characterized in that: In the catalyst, based on the total weight of the MWW molecular sieve and the binder in terms of oxide, the content of the heteropoly acid in terms of the heteropoly acid molecules excluding water is 10 wt % to 100 wt %, preferably 40 wt % to 80 wt %.
5. A method for preparing a catalyst according to any one of claims 1 to 4, comprising the following steps: (1) mixing a silicon source, an aluminum source, an alkali source, water, a first template agent T1 and a second template agent T2, and crystallizing the mixture to obtain an ultra-thin layered MWW molecular sieve; (2) acid-exchanging, shaping, and calcining the ultra-thin layered MWW molecular sieve obtained in step (1) to obtain the catalyst intermediate; (3) The catalyst intermediate obtained in step (2) is impregnated with a heteropolyacid aqueous solution in the presence of a surfactant, and then calcined to obtain the catalyst.
6. The preparation method according to claim 5, characterized in that: The first template agent T1 is selected from at least one of hexamethyleneimine, tetrahydropyrrole, hexahydropyridine, 2-methylhexahydropyridine or heptamethyleneimine, preferably at least one of hexamethyleneimine and hexahydropyridine; the second template agent T2 is selected from at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, didecyldimethylammonium chloride, tetradecyldimethylbenzylammonium chloride, octadecyltrimethylammonium bromide, preferably at least one of hexadecyltrimethylammonium bromide and dodecyltrimethylammonium chloride; And / or, the silicon source is selected from at least one of silicon dioxide, silica sol, white carbon, water glass, sodium silicate or tetraethyl silicate, preferably silicon dioxide. and / or, the aluminum source is selected from at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, aluminum isopropoxide, aluminum sol or aluminum hydroxide, preferably aluminum nitrate; And / or, the alkali source is selected from at least one of sodium hydroxide and potassium hydroxide, preferably sodium hydroxide.
7. The preparation method according to claim 5, characterized in that: In step (1), the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the alkali is calculated as OH - The molar ratio of the feed is: SiO2 / Al2O3 is 10-100, preferably 20-40; OH - / SiO2 is 0-0.40, preferably 0.05-0.15; H2O / SiO2 is 10-50, preferably 20-30; T1 / SiO2 is 0.05-1.0, preferably 0.1-0.5; T2 / SiO2 is 0.001-0.1, preferably 0.01-0.
04.
8. The preparation method according to claim 5, characterized in that: In step (1), the crystallization adopts dynamic crystallization, the stirring rate is 10-200 rpm, preferably 20-100 rpm; the crystallization temperature is 100-200° C., preferably 150-180° C.; the crystallization time is 24-144 h, preferably 48-96 h; And / or, in step (2), the acid exchange conditions include: temperature of 20 to 100° C., preferably 65 to 95° C.; time of 0.5 to 24 h / time, preferably 3 to 8 h / time; acid concentration of 0.001 to 2 mol / L, preferably 0.01 to 0.5 mol / L; acid exchange times of 1 to 6 times, preferably 2 to 4 times; And / or, in step (2), the calcination temperature is 350-650° C., preferably 500-600° C., and the calcination time is 1-10 h, preferably 2-8 h; And / or, in step (3), the calcination conditions are: temperature of 350-550° C., preferably 400-500° C., and time of 1-12 h, preferably 3-6 h.
9. The preparation method according to claim 5, characterized in that: In step (2), the acid is an organic acid and / or an inorganic acid; preferably, the acid is at least one of oxalic acid, citric acid, formic acid, acetic acid, propionic acid, sulfuric acid, nitric acid and hydrochloric acid; and / or, in step (2), the binder used in the molding process is at least one of pseudo-boehmite, silica sol, γ-alumina, aluminum hydroxide or white carbon black, preferably pseudo-boehmite or silica sol; And / or, in step (3), the surfactant is at least one of a nonionic surfactant or an anionic surfactant, preferably, the nonionic surfactant is poly-[ethylene glycol x -Propylene glycol y -Ethylene glycol z ] A triblock oligomer with a molecular weight of 1100 to 14600, preferably 4400 to 8000; the anionic surfactant is one or more of n-hexadecylbenzenesulfonic acid, hexadecyltrimethyltoluenesulfonic acid, and dodecylbenzenesulfonic acid.
10. The preparation method according to claim 5, characterized in that: In step (2), the mass ratio of the acid solution to the molecular sieve is 2 to 20, preferably 5 to 10; And / or, in step (3), the mass ratio of the surfactant to the MWW molecular sieve is 0.001 to 0.10, preferably 0.01 to 0.05; And / or, in step (3), the mass concentration of the heteropolyacid aqueous solution is 8.3% to 83.3%, preferably 33.3% to 66.7%.
11. A method for preparing cyclohexylbenzene by alkylation of benzene and cyclohexene, comprising carrying out an alkylation reaction of benzene and cyclohexene over a catalyst as claimed in any one of claims 1 to 4 to prepare cyclohexylbenzene.
12. The method according to claim 11, characterized in that: The molar ratio of benzene to cyclohexene is 3 to 30, preferably 5 to 15; And / or, the water content in the raw materials benzene and cyclohexene is <100 mg / kg, preferably <50 mg / kg; the total nitrogen content is <0.1 mg / kg, preferably <0.05 mg / kg; the total sulfur content is <0.1 mg / kg, preferably <0.05 mg / kg; And / or, the total mass space velocity of benzene and cyclohexene is 0.1~6.0h -1 , preferably 1.0~4.0h -1 ; The reaction pressure is 1.0 to 4.0 MPa, preferably 1.5 to 2.5 MPa; the reaction temperature is 80 to 200°C, preferably 110 to 150°C.
Citation Information
Patent Citations
Process for producing cyclohexylbenzene
CN101219922A
Method for preparing phenylcyclohexane
CN101811924A
Method for catalytically preparing phenylcyclohexane through acidic ionic liquid [PPh3] [TfOH]2
CN109369322A
Method for preparing cyclohexylbenzene under catalysis of acidic ionic liquid [PPh3][TfOH]3
CN110606796A
Production of phenyl cyclohexane
CN1982263A